RESPON BEBERAPA VARIETAS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (Arachis hypogeae L.) PADA LAHAN GAMBUT - Wira Hadianto; Muhammad Jalil; Teuku Sarwanidas; Zulkifli Zulkifli (Jurnal Agrotek Lestari, 2018)
The aims of the research were determine the effect of the growth and production towards varieties of peanut plants on peat. The research used Randomized Block Design (RBD) pattern of non factorial with four replications. The factor is variety consist of Bison, Naga Umbang, Jerapah, Domba and Gajah. This research was conducted at the experimental field on Teuku Umar University, Meulaboh, Aceh Barat, from April 23 to August 29 2012. The varieties gave very significant effect on the number of branches on 15, 30 and 45 days after planting (DAP), percentage of pods pithy and hollow, are weight of 100 dry seeds. No effect on plant height at 15, 30 and 45 DAP, the number of branches on 15 DAP, one the weight of dry peas. The best growth and yield of peanut found on Jerapah variety and Naga Umbang variety. Keywords: varieties, peatland, peanuts